Chrysophanic acid shifts the differentiation tendency of BMSCs to prevent alcohol‐induced osteonecrosis of the femoral head. (29th June 2020) - Yu, Hongping; Liu, Pei; Zhu, Daoyu; Yin, Junhui; Yang, Qianhao; Huang, Yigang; Chen, Yixuan; Zhang, Changqing; Gao, Youshui
Abstract: Objectives: Osteonecrosis of the femoral head (ONFH), largely caused by alcohol abuse, is a refractory bone disease characterized by the impaired capacity of osteogenic differentiation of bone mesenchymal stem cells (BMSCs), as well as the disordered adipocyte accumulation. Chrysophanic acid (CPA) is a natural anthraquinone which has lipid regulation and bone protection capacity. The aim of this study was to reveal the potential function of CPA and the underlying mechanisms for the alcohol‐induced ONFH. Materials and Methods: The effects of alcohol and CPA on BMSCs were investigated by cell proliferation, induced differentiation assays and immunofluorescent staining. Meanwhile, the function of PI3K/AKT and AMPK pathway was investigated in the process of osteogenic and adipogenic differentiation, respectively. Furthermore, we established the rat model of alcohol‐induced ONFH to reveal the pharmacotherapeutic effect of CPA in vivo using radiographical and histopathological methods. Results: In vitro, alcohol significantly inhibited the proliferation and osteogenic differentiation of BMSCs but stimulated the adipogenic differentiation. However, CPA could counteract the anti‐osteogenesis of alcohol partly via PI3K/AKT pathway and retard the promotion of alcohol‐induced adipogenesis via AMPK pathway. In vivo, radiographical and histopathological findings showed that CPA could alleviate alcohol‐induced ONFH and substantially restore the bone volume. Conclusions: We demonstrated that CPA ameliorated alcohol‐induced ONFH possibly via regulating the differentiation tendency of BMSCs. Hence, CPA may become a beneficial herb extract to alleviate alcohol‐induced ONFH. Abstract : Alcohol impairs the vitality of bone homeostasis within the femoral head, which usually undergoes osteonecrosis with substantial adverse influence on the quality of life. Fortunately, chrysophanic acid (CPA), a natural anthraquinone, can shift the differentiation tendency of bone mesenchymal stem cells, thus to strengthen the capacity of bone formation and retard the pathology of adipocyte accumulation. CPA might become a beneficial herb extract to alleviate alcohol‐induced bone diseases.